Effects of redundant similes on persuasiveness in written arguments - Kudo, Hinako; Onoda, Ryosuke (Frontiers in Education, 2024)
Figurative expressions have been considered beneficial in improving the persuasiveness of arguments; however, little attention has been paid to the effects of those produced by students in writing. This study examined the effects of a "redundant simile," which refers to a simile that merely rephrases the same content in a subtly different manner, on persuasiveness in written arguments. Participants (n = 64) were randomly assigned to control or redundant-simile conditions. A written argument comprised "claim, my-side reason, counterargument, rebuttal, and claim" in both conditions, and a redundant simile was included in "my-side reason" in the redundant-simile condition. The participants evaluated the immediate and delayed persuasiveness of each sentence and rated the confidence of recognition of whether each sentence was used in the evaluation task. The results showed that only the evaluation of the counterargument was significantly higher in the redundant-simile condition than in the control condition. The confidence of recognition of my-side reason was significantly lower in the redundant-simile condition than in the control condition. Thus, redundant similes may negatively affect memory, although they may not directly affect immediate persuasiveness. It is thus important to encourage students to flexibly reflect on their figurative expressions rather than assume that the expressions will always increase persuasiveness.